OpenCV 3 Computer Vision with Python Cookbook : Leverage the power of OpenCV 3 and Python to build computer vision applications. - Spizhevoi, Aleksei (Packt Publishing, 2018)
OpenCV 3 is a native cross-platform library for computer vision, machine learning, and image processing. OpenCV's convenient high-level APIs hide very powerful internals designed for computational efficiency that can take advantage of multicore and GPU processing. This book will help you tackle increasingly challenging computer vision problems ...